Root distribution of Acacia mangium Willd. and Macaranga tanarius L. of rainforest - Avani, Nazi; Lateh, Habibah; Bibalani, Ghassem Habibi (Bangladesh Journal of Botany, 2015)
The number of roots and root area ratio (RAR) decreased with depth in Acacia mangium and Macaranga tanarius and the maximum value of RAR and root number were observed in the first layer of soil. This process was regular in Acacia mangium Willd., but the RAR value showed great variability in Macaranga tanarius L. as the RAR decreased with depth until the second layer (20 cm) and increased again. About 35% of all roots in A. mangium, and about 50% of all roots in M. tanarius are located in the first layer. About 87% of all roots were in the fine root diameter class (d < 2 mm) in M. tanarius species. However 90% of all roots were in the fine root diameter class in A. magnium species. Fine roots contribution to soil reinforcement due to concentration on upper levels, prevent surface erosion and shallow landslide. These results will be useful for slope stability projects. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21665 Bangladesh J. Bot. 43(2): 141-145, 2014 (September)